Pengaruh Gaya Hidup Hedonisme terhadap Perilaku Manajemen Keuangan Mahasiswa - Rafly Satrio; Kiki Anggar Wati; Anardia Destiyana; Rudi Sanjaya (Jurnal Publikasi Ilmu Manajemen, 2024)
Diverse human needs require individuals, especially students, to manage their personal finances wisely. However, the increasingly ingrained hedonistic lifestyle among students has the potential to influence their financial behavior. This study aims to analyze the influence of a hedonistic lifestyle on students' financial management behavior. Students often have greater financial freedom after entering college, but also face challenges in managing their personal finances, especially with increasing access to consumptive consumption. This study uses a quantitative descriptive approach. The results of the analysis show that a hedonistic lifestyle has a negative influence on financial management behavior, where students who tend to have a consumptive lifestyle show lower financial management skills. These findings are expected to be the basis for providing better financial literacy education for students.